Investigating Real‐World Clopidogrel Pharmacogenetics in Stroke Using a Bioresource Linked to Electronic Medical Records. Issue 2 (19th September 2017) - Tornio, Aleksi; Flynn, Rob; Morant, Steve; Velten, Elena; Palmer, Colin N. A.; MacDonald, Thomas M.; Doney, Alex S. F.
Abstract : Clopidogrel efficacy is influenced by genetic variation of cytochrome P450 ( CYP ) 2C19, however, few studies have considered patients who have a stroke. We used electronic medical records (EMRs) linked to a bioresource to examine real‐world implications of clopidogrel pharmacogenetics in stroke. Patients hospitalized for any arterial thrombo‐occlusive (ATO) event who subsequently redeemed clopidogrel prescriptions in the community were entered into the study ( n = 651). During 24‐month follow‐up, the primary endpoint of recurrent ATO or death occurred in 299 patients (46%). CYP2C19*2 loss‐of‐function allele carriers had an increased risk (hazard ratio (HR) = 1.29; 95% confidence interval (CI) = 1.04–1.59; P = 0.019). In the ischemic stroke subgroup ( n = 94), the estimate of risk was greater (HR = 2.23; 95% CI = 1.17–4.24; P = 0.015), which was further supported by a meta‐analysis of available studies. In conclusion, we have demonstrated the clinical impact of CYP2C19*2 on clopidogrel efficacy using a purely EMR approach. This suggests that the risk in the ischemic stroke population may be particularly high.